New Theory Agriculture on Sufficiency Economy Principle as Moderator between Government Policy and Solution of Hevea Brasiliensis Crisis in the Southern Part of Thailand - ทองแกมแก้ว วิศรุตา; จักรภพโยธิน ชนินทร์ (Journal for Developing the Social and Community, 2016)
The study investigated new theory agriculture on Sufficiency Economy principle as a moderator between a government policy and a solution of hevea brasiliensis crisis in the southern part of Thailand.The objectives of this study were to 1) investigate the government policy influencing on the solution of hevea brasiliensis crisis in the southern part of Thailand, 2) investigate the new theory agriculture affecting the solution of hevea brasiliensis crisis in the southern part of Thailand and 3) provide the appropriate methods for solving the hevea brasiliensis crisis in the community level in the southern part of Thailand. The findings showed that 1) there was no significant difference between the influence on the government policy and the solution of hevea brasiliensis crisis in the southern part of Thailand (β =.060, NS), 2) the new theory agriculture with its efficiency at 23%had the influence on the solution of hevea brasiliensis crisis in the southern part of Thailand with the correlation at the 0.01 level of significance, and 3) the government policy and the new theory agriculture with their efficiency at 18% had mutual influence on the solution of hevea brasiliensis crisis in the southern part of Thailand with the correlation at the 0.01 level of significance. The policy suggestions were as follows. 1) The policymakers should have background knowledge and understanding on rubber production as well as administration in rubber plantation as the new theory agriculture, the path of Sufficiency Economy, considering both in procedures and participants’ effects in order to reorganize the policy implementation for the success in assisting agriculturists. 2) Many more projects should be supported and launched so as to drive the public sector and help mutually focus on the advantages of new theory agriculture including the dissemination of the network. 3) In terms of the launch of reinforcement measure together with civil state guidelines, the government conducted the policy promoting the Integrated Farming System and Agroforestry to build together the public network which was driven and assisted by private sectors for better management.